Approximate Boundary Conditions for Patch Antennas Mounted on Thin Dielectric Layers (Communications in Computational Physics, 2020)
In this paper we discuss scattering problems inherent in curved microstrip structures mounted on thin dielectric structures. We provide approximate boundary conditions for such structures in the framework of integral equations.
Keywords: Approximate boundary conditions; boundary integral method; thin dielectric layer; patch antenna.